Evaluation of Investor Behavior: Do Investors Respect their Own Limits? - Braga, Robson; Lima, Gerlando Augusto Sampaio Franco de; De Luca, Márcia Martins Mendes (Contabilidade Vista & Revista, 2015)
In this quasi-experimental study we evaluated the effect of heuristics on financial decision making in order to detect signs of non-rational behavior. At baseline, the participants (=investors) established an anchor percentage value of satisfactory gains and tolerable losses on investment in stock and defined their self-perceived investor profile, but most investors eventually manifested a more aggressive profile, exceeding their own limits considerably. By applying statistics to our findings (Student?s t test and chi-square), we found that, due to analytical biases, overconfidence or unrealistic optimism, investors did not respect their own limits but rather attempted to obtain gains above the initial anchor values. In addition, experiencing a situation of gain or risk did not make a significant difference in the degree of risk the investors were willing to take subsequently, making them accept losses beyond what they initially considered tolerable. Thus, our findings contradict the assumptions of the expected utility hypothesis and the principle of agent rationality.